Análise funcional dos genes xanB e xylA2 de Xanthomonas citri subsp. citri, agente causal do cancro cítrico - Alexandrino, André Vessoni (2020)
Xanthomonas citri subsp. citri (Xcc) is the main bacterium that causes citrus canker, a disease that affects all citrus cultivars of commercial interest, causing damages to the citrus sector due to the decrease in fruit productivity and quality, and the lack of effective control and cure measures. In differential proteomic analysis previously conducted by our research group, phosphomannose isomerase (PMI) and xylose isomerase (XI) were proteins identified as potentially involved in the pathogenesis of citrus canker, the first being detected for the first time on the Xcc surface. Xcc PMI is predicted as a bifunctional enzyme with catalytic activity of interconverting D-mannose-6-phosphate into D-fructose-6-phosphate and D-mannose-1-phosphate to GDP-D-mannose. Xcc XI is also classified as a bifunctional enzyme that interconverts D-xylose into D-xylulose and D-glucose into D-fructose. The present work had as general objective the functional characterization of the coding genes of PMI and XI (xanB and xylA2, respectively), especially regarding the relationship with the Xcc pathogenicity, starting from strategies that involved the construction of IPTG-inducible heterologous expression systems in E. coli, which allowed the confirmation of the predicted biological activities of the target proteins. Homologous double recombination between the genomic DNA and the suicide vector pNPTS138 containing flanking regions of the target gene to be deleted was used to construct mutant strains deleted in the xanB and xylA2 genes (XccΔxanB and XccΔxylA2, respectively). A complementing strain for the first mutant (XccΔCxanB) was successfully obtained by reinserting the gene in the original locus using pNPTS138, an unprecedented methodology in Xcc. In vivo assays in Citrus aurantifolia were conducted using the Xcc, XccΔxanB, XccΔCxanB and XccΔxylA2 strains, which allowed the evaluation of the relationship of the target genes with the Xcc pathogenicity. Deletion of the xylA2 triggered an increase in Xcc virulence, which may be explained by the consequent accumulation of xylose and a possible increase in hrp gene expression. Deletion of the xanB resulted in loss of Xcc pathogenicity, with reduction of its properties related to the infectious process, such as motility, biofilm formation and resistance to ultraviolet radiation, with all these phenotypes being fully restored by gene complementation. Thus, the finding that the xanB is essential for the Xcc pathogenicity makes it a novel and promising target from a biotechnological point of view, providing the perspective of control and/or cure of citrus canker through the use of PMI inhibitors and also the development of citrus cultivars that neutralize the action of such protein during the infectious process.